The Role of Visual Acuity and Segmentation Cues in Compound Word Identification - Hyönä, Jukka (Frontiers in Psychology, 2012)
Studies are reviewed that demonstrate how the foveal area of the eye constrains how compound words are identified during reading. When compound words are short, their letters can be identified during a single fixation, leading to the whole-word route dominating word recognition from early on. Hence, visually marking morpheme boundaries by hyphens slows down processing by encouraging morphological decomposition when holistic processing is a feasible option. In contrast, the decomposition route dominates the early stages of identifying long compound words. Thus, visual marking of morpheme boundaries facilitates processing of long compound words, unless the initial fixation made on the word lands very close to the morpheme boundary. The reviewed pattern of results is explained by the visual acuity principle (Bertram & Hyönä, 2003) and the dual-route framework of morphological processing.